Analisis Peningkatan Profitabilitas Petani Jamur Tiram Melalui Pengembangan Usaha Abon JamurTiram - Yuliana Mariya Ulva; Titi Rapini; Adi Santoso (Universitas Muhammadiyah Ponorogo, 2020)
The purpose of this study was to determine the feasibility of developing the Oyster Mushroom business to be Oyster Mushroom Shredded to increase the profitability of the Oyster Mushroom Farmers and how much is the profitability of Oyster Mushroom farmers before and as young as the development of Shredded Oyster Mushrooms. The location of this study was the